The development of international food aid policy - John Cathie (Intereconomics, 1982)
The European Community is to spend ECU 680 million on food aid in 1982—an increase of 13.3% over 1981. Is this a sign of growing humanitarianism on the part of the EC or merely the side-product of a policy of agricultural protectionism which in the long run is harmful to the economies of both the donors and recipients of food aid? A look at the historical development of international food ald may help to provide an answer to this question.
Keywords: 330; Food Aid